Clinical course of patients with low back pain following an emergency department presentation: A systematic review and meta-analysis - Coombs, Danielle M.; Machado, Gustavo C.; Richards, Bethan; Oliveira, Crystian B. [UNESP]; Herbert, Robert D.; Maher, Chris G. (BMJ, 2021)
Introduction Low back pain, and especially non-specific low back pain, is a common cause of presentation to the emergency department (ED). Although these patients typically report relatively high pain intensity, the clinical course of their pain and disability remains unclear. Our objective was to review the literature and describe the clinical course of non-specific low back pain after an ED visit. Methods Electronic searches were conducted using MEDLINE, CINAHL and EMBASE from inception to March 2019. We screened for cohort studies or randomised trials investigating pain or disability in patients with non-specific low back pain presenting to EDs. We excluded studies that enrolled participants with minimal pain or disability scores at baseline. Two reviewers independently screened the full texts, extracted the data and assessed risk of bias and quality of evidence. Estimates of pain and disability were converted to a common 0-100 scale. We estimated pooled means and 95% CIs of pain and disability as a function of time since ED presentation. Results Eight studies (nine publications) with a total of 1994 patients provided moderate overall quality evidence of the expected clinical course of low back pain after an ED visit. Seven of the eight studies were assessed to have a low risk of bias. At the time of the ED presentation, the pooled estimate of the mean pain score on a 0-100 scale was 71.0 (95% CI 64.2-77.9). This reduced to 46.1 (95% CI 37.2-55.0) after 1 day, 41.8 (95% CI 34.7 to 49.0) after 1 week and 13.5 (95% CI 5.8-21.3) after 26 weeks. The course of disability followed a similar pattern. Conclusions Patients presenting to EDs with non-specific low back pain experience rapid reductions in pain intensity, but on average symptoms persisted 6 months later. This review can be used to educate patients so they can have realistic expectations of their recovery.
Keywords: musculo-skeletal; spine non trauma